2012
DOI: 10.1063/1.4728194
|View full text |Cite
|
Sign up to set email alerts
|

Deep-level photoluminescence due to dislocations and oxygen precipitates in multicrystalline Si

Abstract: We have demonstrated the presence of a dislocation-related component and a component due to oxygen precipitates in a broad deep-level photoluminescence (PL) band in multicrystalline Si at room temperature. In PL intensity mapping, the lower-energy side of the deep-level PL band at about 0.79 eV appeared as a dark line along a small-angle grain boundary (SA-GB) surrounded by a bright band on either side, while the higher-energy side at about 0.87 eV as a bright line along the SA-GB. These intensity variations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
82
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 22 publications
12
82
2
Order By: Relevance
“…On the other hand, the doublet D3/D4 was believed to represent the intrinsic nature of dislocations [8], [15]. This was confirmed recently by Tajima et al [1], [20], who employed micro-PL (μPL) spectroscopy with a high spatial resolution to examine the distribution of D lines around the sub-GBs, finding that D1/D2 were distributed around the sub-GBs, whereas D3/D4 were located directly at the sub-GBs.…”
supporting
confidence: 58%
“…On the other hand, the doublet D3/D4 was believed to represent the intrinsic nature of dislocations [8], [15]. This was confirmed recently by Tajima et al [1], [20], who employed micro-PL (μPL) spectroscopy with a high spatial resolution to examine the distribution of D lines around the sub-GBs, finding that D1/D2 were distributed around the sub-GBs, whereas D3/D4 were located directly at the sub-GBs.…”
supporting
confidence: 58%
“…They also observed pairwise similarity between D1/D2 and D3/D4 regarding their spatial distribution. Oxygen precipitates has also been found to be a possible origin of the D-lines by Pizzini et al 10 and Tajima et al 11 Arguriov 12 proposed D1 and D2 to be generated by transitions between one-dimensional bands on 60…”
Section: B D-linesmentioning
confidence: 97%
“…In contrast, the intensity of the deep-level emissions became strong around SA-GBs. We reported that deep-level emissions at room temperature consist of multiple bands [7]. One deep-level PL labeled D b around 0.87 eV was ascribable to oxygen precipitates.…”
Section: Introductionmentioning
confidence: 94%
“…The intensity of the D b band became higher on SA-GBs, reecting that these grain boundaries acted as preferential precipitation sites for oxygen [7]. Another deep-level PL labeled D a1 around 0.79 eV, which was attributable to secondary defects or impurities attracted by a strain eld around SA-GBs, appeared as bright bands surrounding SA-GBs [7]. Objectives of the present study were to investigate the relationship between these deep-level emissions and the density of SA-GBs and to identify the origin of the D b band emission.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation